Joint Action of Wind and Temperature on Long-Span Concrete-Filled Steel Tube Bridges in the Yellow River Basin - Jiang Liu; Haotian Wu; Huajun Guo; Zhiyuan Ma; Feixiang Zheng; Yinping Ma; Yongjian Liu (Buildings)
Complex wind and temperature characteristics in the Yellow River basin (YRB) challenge the safety and durability of long-span concrete-filled steel tube (CFST) bridges greatly. To address this issue, it is important to accurately assess the joint actions of wind and temperature. In this paper, the joint actions of wind and temperature in eight typical YRB cities are analyzed. The joint distributions of wind speed and air temperature are developed with the Archimedean Copula, and the Kendall return period is used for occurrence probability estimations. Eight wind–temperature combinations are considered. Responses for these combinations are calculated and compared with specification actions. Results show significant wind–temperature variations in the YRB. When wind actions adopt the univariate representative values (URVs), the temperature actions are reduced by 20–40%; when temperature actions use URVs, wind actions experience a reduction by more than half of their URVs. The joint responses can sometimes exceed, but are mostly less than, the specification responses, with a maximum strength margin over 11 MPa. These efforts suggest that the proposed joint actions can expand the provisions in the General Specification and provide guidance for the design of long-span CFST bridges.